2022
DOI: 10.1098/rsos.211491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the kinematics for kangaroo rat hopping on a solid versus sand surface

Abstract: In their natural habitats, animals move on a variety of substrates, ranging from solid surfaces to those that yield and flow (e.g. sand). These substrates impose different mechanical demands on the musculoskeletal system and may therefore elicit different locomotion patterns. The goal of this study is to compare bipedal hopping by desert kangaroo rats ( Dipodomys deserti) on a solid versus granular substrate under speed-controlled conditions. To accomplish this goal, we developed a rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…For example, eels differ in their kinematics and performance when moving terrestrially on sand vs. pebble substrates (Mehta et al, 2020;Redmann et al, 2020), box turtles have shorter strides and lower speeds on sand than on Styrofoam (Claussen et al, 2002), human athletes use different ankle and hip joint kinematics during squat jumps on rigid vs. sand surfaces (Giatsis et al, 2004), and a cursorial gecko species was shown to change its body angle and duty factor during transitions from firm to sand surfaces (Naylor and Higham, 2022). On the other hand, one experiment showed that kangaroo rats could hop at 1.8 m s -2 on either sand or a solid surface without changing any of the kinematic variables that were measured (hop period, hop length, duty cycle) (Hall et al, 2022). Even within granular media, variation in physical characteristics can affect locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, eels differ in their kinematics and performance when moving terrestrially on sand vs. pebble substrates (Mehta et al, 2020;Redmann et al, 2020), box turtles have shorter strides and lower speeds on sand than on Styrofoam (Claussen et al, 2002), human athletes use different ankle and hip joint kinematics during squat jumps on rigid vs. sand surfaces (Giatsis et al, 2004), and a cursorial gecko species was shown to change its body angle and duty factor during transitions from firm to sand surfaces (Naylor and Higham, 2022). On the other hand, one experiment showed that kangaroo rats could hop at 1.8 m s -2 on either sand or a solid surface without changing any of the kinematic variables that were measured (hop period, hop length, duty cycle) (Hall et al, 2022). Even within granular media, variation in physical characteristics can affect locomotion.…”
Section: Discussionmentioning
confidence: 99%